ANALISIS POSTUR KERJA PEGAWAI PADA LINE PACKING REFRIGERATOR DENGAN METODE RAPID UPPER LIMB ASSESSMENT (RULA) DI PT. XYZ - Tungga, Riananda Dwismara; Herwanto, Dene; Nugraha, Billy (Teknik Industri Unikom, 2021)
Manual work activities are at risk for musculoskeletal disorders. Manual material handling, including lowering, lifting, pulling and carrying activities is the cause of worker complaints. Conditions of work attitude at PT. XYZ in the packing section, which is in charge of taking out the refrigerator cardboard, is still at risk. The posture of employees is bent, standing with arms stretched upwards and standing with arms stretched upwards. The purpose of this study is to suggest improvements in work attitude by making tools for work postures that are not ergonomic. The method used in this study is the rapid upper limb assessment (RULA). Based on the results of data processing, it can be concluded that the standing work posture on the cardboard lifting activity element gets a grand score of 4. This means that it is at a moderate risk level and improvements can be made if needed. The working posture of walking with hands carrying cardboard has a grand score of 7. This means that it is at a high risk level and must be corrected immediately. To reduce non-ergonomic work postures. Then a design tool is made in the form of an insulated trolley.